2018
DOI: 10.1007/s11524-018-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Index of Concentration at the Extremes as Indicators of Structural Racism to Evaluate the Association with Preterm Birth and Infant Mortality—California, 2011–2012

Abstract: Disparities in adverse birth outcomes for Black women continue. Research suggests that societal factors such as structural racism explain more variation in adverse birth outcomes than individual-level factors and societal poverty alone. The Index of Concentration at the Extremes (ICE) measures spatial social polarization by quantifying extremes of deprived and privileged social groups using a single metric and has been shown to partially explain racial disparities in black carbon exposures, mortality, fatal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 62 publications
7
153
2
Order By: Relevance
“…Similar to previous studies among Black pregnant women, women in the present study most frequently reported experiencing racial discrimination in public settings (e.g., school, on the streets; Canady et al, 2008;Ertel et al, 2012). We also found that there was no significant difference between neighbourhood race + income extremes and experiencing racial discrimination getting hired or get- We found that Black women who lived in neighborhoods with the most deprived race + income concentrations were more likely to have a preterm birth or experience an infant death in comparison with Black women who lived in neighborhoods with the most privileged race + income concentrations (Chambers et al, 2018). These data suggest that women in this study maybe at higher risk for adverse birth outcomes due to high exposures to both interpersonal and structural racism.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar to previous studies among Black pregnant women, women in the present study most frequently reported experiencing racial discrimination in public settings (e.g., school, on the streets; Canady et al, 2008;Ertel et al, 2012). We also found that there was no significant difference between neighbourhood race + income extremes and experiencing racial discrimination getting hired or get- We found that Black women who lived in neighborhoods with the most deprived race + income concentrations were more likely to have a preterm birth or experience an infant death in comparison with Black women who lived in neighborhoods with the most privileged race + income concentrations (Chambers et al, 2018). These data suggest that women in this study maybe at higher risk for adverse birth outcomes due to high exposures to both interpersonal and structural racism.…”
Section: Discussionmentioning
confidence: 52%
“…Structural racism in the U.S. context has been historically used to advantage Whites over Blacks in society through the implementation of discriminatory practices such as redlining, which have been proven to limit access to housing, quality education, wealth, employment, and disproportionate incarceration rates (Bailey et al, 2017;Gee & Ford, 2011;Jones, 2001;Massey & Denton, 1988;Mehra et al, 2017;Ncube et al, 2016;White & Borrell, 2011). Research consistently shows that higher exposures to structural racism is associated with adverse birth outcomes among Black women even after controlling for individual level characteristics (Chambers et al, 2018;Iceland & Wilkes, 2006;Mehra et al, 2017;Ncube et al, 2016;White & Borrell, 2011). However, it remains unknown if Black women's exposure to structural racism is related to racial discrimination experienced in specific situational domains.…”
Section: Introductionmentioning
confidence: 99%
“…38 Given structural racism, loss of trust in the healthcare system, and mistreatment during pregnancy and childbirth, women of colour suffer from appallingly poor perinatal outcomes such as increased rates of maternal death and preterm birth compared with non-Hispanic white women. [39][40][41][42][43] Support during labour has been linked to lower rates of caesarean section, higher 5 min Apgar scores and increased patient satisfaction; policies that reduce support may further exacerbate these disparities. 44 Disparities in women's health may also be exacerbated by the public health response to COVID-19 in other arenas.…”
Section: Health Outcomes Disparitiesmentioning
confidence: 99%
“…Conversely, maternal and neighborhood factors did not strongly influence NICU outcomes in the New York City study, though they are known risk factors to adverse birth outcomes including preterm birth [46]. Analyses of associations between zip-code level racial and economic segregation and preterm birth and infant mortality in California showed that women and infants in less privileged zip codes were at increased odds for these adverse outcomes [47]. The contributions of such multilevel resources have also been demonstrated in other areas of health; in particular, this is an emerging area of research in cancer epidemiologic studies [48,49].…”
Section: Discussionmentioning
confidence: 78%